2021
DOI: 10.1093/mnras/stab292
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the target selection pipeline for the Dark Energy Spectroscopic Instrument Bright Galaxy Survey

Abstract: We present the steps taken to produce a reliable and complete input galaxy catalogue for the Dark Energy Spectroscopic Instrument (DESI) Bright Galaxy Sample (BGS) using the photometric Legacy Survey DR8 DECam. We analyze some of the main issues faced in the selection of targets for the DESI BGS, such as star-galaxy separation, contamination by fragmented stars and bright galaxies. Our pipeline utilizes a new way to select BGS galaxies using Gaia photometry and we implement geometrical and photometric masks th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
0
22
1
Order By: Relevance
“…A candidate BGS selection using DR8 DECaLS was first explored in (Ruiz-Macias et al 2021) and also in a research note (Ruiz-Macias et al 2020). The core of this selection for the bright sample remains unchanged: a bright sample at 𝑟 < 19.5 (BGS Bright) and a faint sample at 19.5 < 𝑟 < 20 (BGS Faint).…”
Section: Bgs Target Catalogue Using Dr9mentioning
confidence: 99%
See 3 more Smart Citations
“…A candidate BGS selection using DR8 DECaLS was first explored in (Ruiz-Macias et al 2021) and also in a research note (Ruiz-Macias et al 2020). The core of this selection for the bright sample remains unchanged: a bright sample at 𝑟 < 19.5 (BGS Bright) and a faint sample at 19.5 < 𝑟 < 20 (BGS Faint).…”
Section: Bgs Target Catalogue Using Dr9mentioning
confidence: 99%
“…In Section 2.3, we investigate the consequences of such a change in the BGS selection (ii) Large galaxies: the size of the masking radius around large galaxies in DR9 has increased from roughly 10 arsec to 30 arcsec, however the pre-fitting for large sources led to major improvements in the photometry extraction of these objects which allows us not to apply this mask in DR9. Moreover, we remind the reader that in (Ruiz-Macias et al 2021), we assess the completeness of the previous selection using DR8 by matching the BGS targets with GAMA DR4 and found that we were missing about 25 true galaxies/deg 2 .…”
Section: Changes In the Bgs Target Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…While this kind of bias may be expected, it is important to characterize and take into account. One solution is to acquire more training data where current data are sparse; in the future, we will be able to alleviate the CNN biases by incorporating data from massively multiplexed spectroscopic surveys such as the DESI Surveys (DESI Collaboration et al 2016;Ruiz-Macias et al 2021;E. Darragh-Ford et al, in preparation).…”
Section: Cross-validationmentioning
confidence: 99%